Humour and Leadership at School - Adão, Teresa (2011)
Humour and Leadership at School This study establishes a relationship between the capacity of humour appreciation and the way leadership is held at school. The individual leadership characteristics of some school leaders have been compared with their sense of humour and although the results haven’t been very conclusive, there is a strong tendency, showing that school headmasters who are true leaders reveal a good sense of humour. In methodological terms, this study was organized in two phases: in the first one, 85 headmasters answered to a questionnaire built in order to evaluate their leadership characteristics; in the second phase, 50 headmasters chosen among the initial 85 because of their good capacity of leadership were evaluated, taking into account Thorson and Powell sense of humour scale (1993). This experimental research enables us to conclude that there is a moderate positive correlation between sense of humour and the dominance personality of a leader as far as school environment is concerned.